A Qualitative Approach to Understanding the Holistic Experience of Psychotherapy Among Clients - Seow, Lee Seng Esmond; Sambasivam, Rajeswari; Chang, Sherilyn; Subramaniam, Mythily; Lu, Huixian Sharon; Assudani, Hanita Ashok; Tan, Chern-Yee Geoffrey; Vaingankar, Janhavi Ajit (Frontiers in Psychology, 2021)
Background: The study of the experience of clients across multiple service encounters (or touchpoints) is important from the perspective of service research. Despite the availability of effective psychotherapies, there exists a significant gap in the optimal delivery of such interventions in the community. Therefore, the aim of this study was to explore the experience of psychotherapy among clients integrating the before–during–after service encounters using a qualitative approach. Methods: A total of 15 clients of outpatient psychotherapy were interviewed, and data saturation was reached. The topics included pathways and reasons to seeking psychotherapy, aspects of the therapy process that have been helpful or unhelpful, and perceived change after receiving psychotherapy. Information was analyzed using the inductive thematic analysis method. Emergent themes pertaining to pre-psychotherapy encounters were mapped onto major components that were identified in Andersen's Health Service Utilization Model. Results: Mental health stigma and the lack of understanding about psychotherapy were the predisposing factors that impeded service use while the preference for non-pharmacological intervention promoted its use. Enabling factors such as affordability and service availability were also of concern, along with perceived and evaluated needs. The attributes of therapists, application of techniques, and the resistance of the client were found to impact the therapeutic alliance. While the majority of the clients experienced positive change or had engaged in self-help strategies after receiving psychotherapy, some cited limited impact on the recovery of symptoms or problematic self-coping without the therapists. Conclusion: This study proposes to expand on Andersen's Behavioral Model by including therapy-related factors so as to provide a more holistic understanding of the use of psychotherapy among the clients. More importantly, the study identified several barriers to access and negative experiences or outcomes, which should be addressed to promote uptake of the psychotherapy intervention.